Promotion of Self-Discipline of Students Studying in the 4th – 6th Primary Classes of the Schools Under Local Administrative Organization, Namphong District, Khonkaen Province - Armart, Kanyaporn (Academic MCU Buriram Journal, 2017)
The objectives of the research were to study and find out the guideline for development of How to Promote Being Self-Discipline of Students Studying in the 4th – 6th Primary Classes of the Schools under Local Administrative Organization, Namphong District, Khon Kaen Province. The sampling used for the research were educational administrators, teachers, committee of basic education schools, and students’ parents totaling 113 people.The tools used for the research were questionnaires with rating scales, and the data used for studies’ method were primary data, that is the data derived from questionnaires. The statistics used for data analysis was Frequency, Percentage, Mean, and Standard Deviation. The findings were as followed: How to Promote Being Self-Discipline of Students Studying in the 4th – 6th Primary Classes of the Schools under Local Administrative Organization, Namphong District, Khon Kaen Province was at high level in both total aspect and each aspect, when arranging from high to low level it was found that it was prioritized in accordance with averaged value in the followings: 1) Environmental condition of schools 2) Social condition around the schools 3) The aspect involving with how to take care for the students of their parents respectively. 2. As for the guideline for development of How to Promote Being Self Discipline of Students Studying in the 4th – 6th Primary Classes of the Schools under Local Administrative Organization, Namphong District, Khon Kaen Province, it should be made as follows: 1) For environmental condition of the schools, the students should be encouraged to participate the schools’ activities in both internal and external activities formulated by the schools in continuation basis for responsibility 2) for social condition, the cooperation of many sectors should be made to have all the students get good opportunity to participate the social activities 3) for the taking care of the students the students’ parents should be interested in their children more than it was, the parents should open their minds to let their children express their opinions freely trying to encourage and support them to participate the useful activities no matter what they are, and the parents should take more times for cooperation with their children than before.